Synthesis and controlled growth of osmium nanoparticles by electron irradiation. Issue 47 (29th September 2015) - Pitto-Barry, Anaïs; Perdigao, Luis M. A.; Walker, Marc; Lawrence, James; Costantini, Giovanni; Sadler, Peter J.; Barry, Nicolas P. E.
Abstract : Defined-size osmium nanoparticles (1.5–50 nm) were synthesized on a B- and S-doped turbostratic graphitic structure from an organometallic osmium complex encapsulated in self-spreading polymer micelles and characterised by (HR)TEM, AFM and XPS. Abstract : We have synthesised osmium nanoparticles of defined size (1.5–50 nm) on a B- and S-doped turbostratic graphitic structure by electron-beam irradiation of an organometallic osmium complex encapsulated in self-spreading polymer micelles, and characterised them by transmission electron microscopy (TEM), high-resolution TEM (HRTEM), and atomic force microscopy (AFM) on the same grid. Oxidation of the osmium nanoparticles after exposure to air was detected by X-ray photoelectron spectroscopy (XPS).